Passando o bastão : a nova geração de liberais brasileiros - Camila Rocha (Centre de Recherches sur les Mondes Américains, 2017)
In this article I argue that it has emerged in Brazil a new generation of liberals whose modus operandi is different from that of the older generation, in the sense that it’s political behavior is analogous to contemporary social movements. To sustain this argument, I will base myself on interviews with leaders and activists of the movement, publicly available information on social networks, websites and blogs, and historical documents of liberal think tanks collected in a field research still in progress regarding a case study of the Brazilian liberal movement. In the article’s first section I point out the characteristics of the Brazilian liberal movement that lasted from the 1980s until the mid 2000s, and in the second section, what are the novelties presented by the liberal youth.